Development and validation of a rapid gas chromatography for simultaneous quantification of major fatty acids in royal jelly - Xinyu Yu; Wenting Wei; Yuqi Wu; Yuanyuan Lu; Fuliang Hu; Shanshan Li (Food Science of Animal Products)
Fatty acids are distinctive components of royal jelly (RJ), serving as a crucial indicator for assessing the quality of RJ. This study aimed to establish a rapid and simultaneous quantification method for various fatty acids in RJ utilizing gas chromatography. An optimized two-step extraction process, incorporating ethanol and diethyl ether followed by derivatization with N,O-bis-(trimethylsilyl) trifluoroacetamide, was developed to enhance sensitivity and precision in detecting fatty acids. Validation of the methodology revealed excellent linearity (R2 > 0.999), precision (relative standard deviation (RSD) < 1%), repeatability (RSD < 1%), and recoveries (94.4%–104%). Furthermore, the limits of detection and quantification were found to be low. The results indicated that the method offered reliable and consistent quantification of major fatty acids, thereby improving quality control for RJ and facilitating its applications in food, pharmaceutical, and biochemical research.